Advances in Boundary Value Problems for Fractional Differential Equations (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint covers new aspects of the recent developments in the theory and applications of fractional differential equations, including inclusions, inequalities, and systems of fractional differential equations with Riemann-Liouville derivatives, Caputo derivatives, or other generalized fractional derivatives, subject to various boundary conditions. The authors study the existence, uniqueness, multiplicity, and nonexistence of classical or mild solutions, the approximation of solutions, and the approximate controllability of mild solutions for diverse mathematical models.